An experiment on the impact of weather shocks and insurance on risky investment - Hill, Ruth Vargas; Viceisza, Angelino (International Food Policy Research Institute, 2010)
We conduct a framed field experiment in rural Ethiopia to test the seminal hypothesis that insurance provision induces farmers to take greater, yet profitable, risks. Farmers participated in a game protocol in which they were asked to make a simple decision: whether to purchase fertilizer, and if so, how many bags. The return to fertilizer was dependent on a stochastic weather draw made in each round of the game protocol. In later rounds of the game protocol, a random selection of farmers made this decision in the presence of a stylized weather-index insurance contract. Insurance was found to have some positive effect on fertilizer purchases. Purchases were also found to depend on the realization of the weather in the previous round. We explore the mechanisms of this relationship and find that it may be the result of both changes in wealth weather brings about and changes in perceptions of the costs and benefits of fertilizer purchases.